Iron-containing binder for metallurgical pellet preparation and preparation method of iron-containing binder

The preparation of new iron-containing binders by compounding bentonite and cobalt smelting waste slag has been solved, and the problem of reducing iron content in pelletized ore and difficult to utilize cobalt smelting waste slag is achieved, and the effect of improving the iron grade and compressive strength of pelletized ore, reducing production costs and environmental pollution is achieved.

CN119592790APending Publication Date: 2025-03-11ANHUI METALLURGICAL TECH VOCATIONAL COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411339817.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The residual effect of the binder used in existing pellet ore under high temperature conditions leads to a decrease in iron content and an increase in silicon content, increasing the energy consumption of iron smelting and flux costs. At the same time, cobalt smelt waste slag is difficult to be used in resource utilization.

Method used

A new type of iron-containing binder is prepared by compounding bentonite and cobalt smelting waste slag, using the layered structure of bentonite and Fe(OH)3 in cobalt smelting waste slag to form a gel, improving the iron grade and compressive strength of the pellet ore, and realizing the resource utilization of cobalt smelting waste slag.

Benefits of technology

It significantly improves the iron grade and compressive strength of the pellet ore, reduces the amount and production cost of bentonite, realizes harmless treatment and resource utilization of cobalt smelting waste slag, and improves the economic benefits of iron smelting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592790A_ABST
    Figure CN119592790A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-containing binder for metallurgical pellet preparation and a preparation method of the iron-containing binder, and belongs to the technical field of metallurgy. The iron-containing binder comprises the following components: 20-50% of cobalt smelting waste residue and 50-80% of bentonite. The preparation method of the iron-containing binder comprises the following steps: step 1, weighing the bentonite, and adding water to prepare a turbid liquid; 2, cobalt smelting waste residues are added into the turbid liquid, sufficient stirring is conducted, and standing is conducted for a period of time; and 3, carrying out separation and purification by using a centrifugal machine, compacting the purified solid matter, extruding by using a screw extruder, and loading into a sample bag for aging after the extrusion is completed. 4, after aging is completed, drying, smashing and sieving are conducted, and then the iron-containing binder is obtained, the binder is good in binding performance and few in residue, when the binder is used for iron ore pellet preparation, the strength of roasted pellets and the iron grade of pellet ore can be remarkably improved, the iron-making economic benefits are improved, and volume reduction, harmless and resourceful treatment of cobalt smelting waste residues is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and more specifically, relates to an iron-containing binder for preparing metallurgical pellets and a preparation method thereof. Background Art

[0002] With the increasingly stringent requirements of modern blast furnaces on the fineness of raw materials and the simplification of steel production processes, pellets have become an irreplaceable high-quality metallurgical raw material in the steel industry. The quality and production cost of pellets are the main obstacles to reducing the current pre-iron process costs.

[0003] In the process of pellet production, a binder is needed to achieve the purpose of pellet hardening. At present, bentonite is widely used as a binder in the pellet production industry, which has good ball-forming properties and the advantages of low cost and easy access. However, the residual effect of bentonite under high temperature conditions will lead to a decrease in the iron content and an increase in the silicon content in the raw materials entering the furnace, which not only increases the energy consumption in the iron-making process, but also increases the cost of flux. This situation has prompted the industry to actively seek new bonding materials to improve the quality of pellets while reducing the adverse effects on the steel production process.

[0004] After searching, a large number of patents have disclosed binders used in pelletizing ore. For example, the Chinese patent publication number is CN115094235B, and the publication date is September 23, 2022. It discloses a bentonite binder and its preparation method and application. The new bentonite binder is prepared by mixing pure bentonite, acrylamide, starch, sodium carbonate and potassium permanganate.

[0005] For another example, the Chinese patent publication number is CN101693950B, and the publication date is April 14, 2010. It discloses a polymer-type iron ore pellet organic binder and a method of using the same. The binder is prepared by mixing sodium humate, sodium fulvic acid and borax.

[0006] For another example, the Chinese patent publication number is CN104357656A, and the publication date is February 18, 2015. It discloses an organic binder and pellets for blast furnace ironmaking produced using the same. Rice, broken rice, glutinous rice, and corn are used as raw materials separately, and calcium-based bentonite is added after treatment to prepare the binder.

[0007] The technical solution disclosed in the above application can reduce the amount of bentonite used to a certain extent and improve the TFe grade of the finished pellet ore. However, due to the low profit margin of domestic steel mills, the above binder uses more chemical raw materials, which increases the production cost. This brings certain difficulties to the promotion and application of composite pellet binders in China. Summary of the invention

[0008] 1. Problem to be solved

[0009] The purpose of the present invention is to provide an iron-containing binder for metallurgical pellets and a preparation method thereof, wherein the iron-containing binder has good bonding performance and less residue, and the composite binder is applied to the preparation of iron ore pellets, which can significantly improve the strength of roasted pellets, improve the iron grade of pellets, and improve the economic benefits of ironmaking, and at the same time effectively solve the problem that cobalt smelting waste slag is difficult to recycle. Finally, pellets with good performance indicators such as green ball falling and compressive strength, roasted pellet compressive strength, etc. are produced, and the volume reduction, harmlessness, and resource treatment of cobalt smelting waste slag are achieved.

[0010] 2. Technical solution

[0011] In view of the deficiencies of the binders used in the existing pellets as described in the above background technology, the present invention creatively proposes a new type of iron-containing binder. By compounding bentonite and cobalt smelting waste slag, the strength of the roasted pellets and the iron grade of the pellets can be effectively improved, and the economic benefits of ironmaking are good. The cobalt smelting waste slag used in the present invention is a solid waste slag produced in the purification process of the hydrometallurgical cobalt smelting process. The applicant has found through a large number of experimental studies that the cobalt smelting waste slag can be used as a binder for metallurgical pellets, using Fe(OH)3 contained in the cobalt slag. Fe(OH)3 is used as a hydrophilic substance, which can form a gel to bond the iron ore particles, but it will decompose and release H2O during the preheating and roasting process of the pellets, causing the internal vapor pressure of the pellets to increase, causing the pellets to crack, resulting in a decrease in the explosion temperature of the pellets after adding the cobalt smelting waste slag. Therefore, in the prior art, cobalt smelting waste slag is rarely used in the production of blast furnace pellets. The applicant has found through research that cobalt smelting waste slag cannot be directly added to the binder for use as a composite binder. The cobalt smelting waste slag and bentonite must be processed to prepare the novel iron-containing binder of the present invention for use. This not only solves the problem that the prior art uses bentonite as a binder to manufacture pellets, but also solves the problem that the iron content in the raw materials entering the furnace is reduced and the silicon content is increased, which has an adverse effect on the energy consumption of ironmaking. In addition, the technical solution of the present invention also realizes the disposal and resource utilization of cobalt smelting waste slag, and the following advantages are achieved in the production of pellets:

[0012] (1) The iron grade of the pellets is improved, and the compressive strength of the pellets is further improved;

[0013] (2) Reduce the amount of bentonite used and reduce production costs;

[0014] (3) The harmless treatment of cobalt smelting waste slag is achieved, avoiding the harm caused by cobalt smelting waste slag to the environment and human health.

[0015] Specifically, the technical solution adopted by the present invention is as follows:

[0016] The present invention provides an iron-containing binder for metallurgical pellets, which is composed of the following components in terms of dry weight percentage: 20% to 50% of cobalt smelting waste slag and 50% to 80% of bentonite. The preparation method of the iron-containing binder comprises the following steps:

[0017] Step 1, weigh bentonite and add it into a suspension according to a certain solid-liquid ratio;

[0018] Step 2: Add cobalt smelting waste slag to the suspension, stir it thoroughly, disperse the cobalt smelting waste slag in water, enter the gel formed by bentonite particles, and let it stand for a period of time;

[0019] Step 3: Separate and purify the bentonite suspension containing cobalt smelting waste by using a centrifuge, compact the purified solids and extrude them by using a screw extruder, and after the extrusion is completed, put them into a sample bag for aging.

[0020] Step 4: After aging, the mixture is dried in an oven, crushed in a ball mill, and sieved to obtain an iron-containing binder.

[0021] The present invention pre-treats cobalt smelting waste slag and bentonite, utilizes the montmorillonite layered structure in the bentonite, decomposes Fe(OH)3 to form H2O, and orderly guides it out with the help of the layered structure channel of the bentonite, thereby avoiding the problem of the pellet bursting temperature dropping. At the same time, the iron-containing binder contains elements such as Ca, Fe, Si, etc. to form composite calcium ferrite during pellet roasting, and forms a liquid phase inside the roasted pellet, which is conducive to solid phase diffusion, promotes the recrystallization of hematite at high temperature, and forms a large area of ​​hematite crystals. After adding the iron-containing binder of the present invention, the hematite grain size in the pellet can be enlarged, the connection is more dense, and the holes between the grains are significantly reduced. The iron-containing bonding of the present invention can make the roasted pellets obtained have better compressive strength indicators.

[0022] As a further preferred embodiment of the present invention, the particle size composition of the cobalt smelting waste slag and bentonite is that particles smaller than 0.074 mm account for more than 98%.

[0023] As a further preferred embodiment of the present invention, the mass content of Fe(OH)3 in the cobalt smelting waste slag is not less than 30% of the total amount.

[0024] As a further preferred embodiment of the present invention, in step (1), the mass ratio of the cobalt smelting waste slag to the bentonite dry material is 1:1 to 1:4.

[0025] As a further preferred embodiment of the present invention, in step (1), bentonite is added into water at a solid-to-liquid ratio of 1:(5-8).

[0026] As a further preferred embodiment of the present invention, after adding the cobalt smelting waste slag into the suspension, the suspension is left to stand for 1-2 hours.

[0027] As a further preferred embodiment of the present invention, the aging time in step (3) is 2 to 3 days.

[0028] As a further preferred embodiment of the present invention, in step (4), the iron-containing binder has a particle size composition of particles smaller than 0.074 mm accounting for more than 98%.

[0029] The iron-containing binder prepared by the preparation method of the present invention is added into the pelletizing material for pelletizing, and the adding proportion accounts for 1-2% of the total mass of the pelletizing material.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The present invention prepares a new type of iron-containing binder by mixing cobalt smelting waste slag generated by the cobalt smelting industry with bentonite, which not only realizes the efficient resource utilization of cobalt smelting waste slag, but also provides a new way for the digestion of cobalt smelting waste slag, thereby reducing the harm of the waste slag to the environment and human body.

[0032] (2) The present invention optimizes the pretreatment method of cobalt smelting waste slag and bentonite. Compared with conventional mechanical mixing, the bentonite is first configured into a suspension, the cobalt smelting waste slag is added to the suspension and allowed to stand, and then a centrifuge is used for separation and purification. The separated and purified solids are then extruded by a screw extruder, and finally aged to obtain an iron-containing binder. The method of the present invention can effectively ensure the bonding effect of cobalt smelting waste slag and bentonite.

[0033] (3) Compared with the prior art that uses bentonite as a binder, the iron-containing binder used in the present invention for pelletizing can reduce the amount of SiO2 and Al2O3 brought into the pellets, reduce the amount of blast furnace ironmaking slag, and ultimately reduce the production cost of steel enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a graph showing the hydrophilic contact angle test results of a mixture of 2% iron-containing binder A + 98% magnetite;

[0035] Figure 2 This is a graph showing the hydrophilic contact angle test results of a mixture of 2% iron-containing binder B + 98% magnetite; DETAILED DESCRIPTION

[0036] The invention discloses an iron-containing binder for metallurgical pellets and a preparation method thereof. The iron-containing binder is prepared from a mixture of cobalt smelting waste slag and bentonite, the prepared iron-containing binder is used as a pellet binder, and the prepared iron-containing binder is evenly mixed with a pellet material and then water is added to prepare green pellets. The green pellets are dried, preheated and roasted to prepare roasted pellet products, which can be used in blast furnaces.

[0037] It should be noted that direct mechanical mixing of cobalt smelting waste slag and bentonite will result in insufficient mixing. The cobalt smelting waste slag and bentonite are only mechanically meshed at the physical level. In particular, Fe(OH)3 will decompose to form H2O during the pellet preheating stage. When H2O cannot be fully discharged, the bursting temperature will be reduced. To solve this problem, the applicant has found through a large number of experiments that, first, the bentonite is configured into a suspension, and then the cobalt smelting waste slag is added to the bentonite suspension and stirred sufficiently. This operation can utilize the gel formed by adding water to the bentonite and the Fe(OH)3 in the cobalt smelting waste slag to form a suspension. OH)3 is combined with the gel formed by the two materials to form a whole, which improves the bonding effect between the mixed materials, thereby forming a more hydrophilic binder material; then, a centrifuge is used for separation and purification, and the purified solids are compacted and then extruded using a screw extruder. Through this operation, it is convenient to use the screw extrusion process, so that the bentonite is simultaneously subjected to the effects of extrusion and shear force, so that part of the montmorillonite crystal layer is pushed open, and the multi-layer structure is changed into a single-layer sheet structure, which has good fibrous connection characteristics, thereby significantly improving the mixing effect of cobalt smelting waste slag and bentonite. Finally, it is placed in a sample bag for aging treatment. Through aging treatment, the cobalt smelting waste slag can be further infiltrated into the interlayer of bentonite, and the interlayer expansion effect will be further enhanced, thereby effectively utilizing the montmorillonite layered structure in the bentonite, and it is convenient to orderly export the H2O formed by the decomposition of Fe(OH)3 with the help of the layered structure channel, thereby avoiding the problem of the decrease in the burst temperature of the pellets.

[0038] In addition, compared with conventional bentonite binders, the iron-containing binder prepared by the present invention not only reduces the amount of SiO2 and Al2O3 brought into the pellet ore, but also can significantly improve the comprehensive performance of the prepared pellets, especially the compressive strength and iron grade of the prepared roasted pellet products, thereby helping to reduce the amount of blast furnace ironmaking slag, and also realizes the volume reduction, harmlessness and resource utilization of cobalt smelting waste slag.

[0039] Specifically, the iron-containing binder of the present invention is composed of the following components in terms of dry weight percentage: 20% to 50% of cobalt smelting waste slag and 50% to 80% of bentonite. The preparation method of the iron-containing binder comprises the following steps:

[0040] Step 1, weigh bentonite, and add the bentonite into water according to a solid-liquid ratio of 1:(5-8) to prepare a suspension;

[0041] Step 2: The dry material mass ratio of smelting waste slag to bentonite is 1: (1-4), and cobalt smelting waste slag is added to the suspension, and the iron-containing binder particle size composition is more than 98% of particles less than 0.074 mm, and the cobalt smelting waste slag is fully stirred to disperse in water and enter the gel formed by bentonite particles and stand for 1-2 hours;

[0042] Step 3: Separate and purify the bentonite suspension using a centrifuge, and extrude the solid matter using a screw extruder after compaction. After extrusion, the solid matter is placed in a sample bag and aged for 2 to 3 days.

[0043] Step 4: After aging, the mixture is dried in an oven, crushed in a ball mill, and sieved to obtain an iron-containing binder.

[0044] To further illustrate the iron-containing binder prepared in the present invention, the present invention adds the iron-containing binder into a pelletizing material to produce pellets, the pelletizing material used is magnetite powder, and the performance of the produced green balls and roasted pellet products is tested.

[0045] The specific steps for testing the drop strength of the raw ball are as follows:

[0046] Step S1, select 12 green balls of similar size, test one green ball each time, and let it fall freely from a height of 0.5m onto a 10mm thick steel plate. Counting starts from 0 times, and repeat the drop test until cracks appear on the green ball, which is the number of drops. Calculate the average value as the green ball drop strength.

[0047] Step S2: Testing the compressive strength of green balls

[0048] The green ball compressive strength test is carried out on the green ball compressive strength tester (YHKC 2A model) according to ISO 700 standard. Twelve green balls of similar size are selected, one green ball is tested each time, and the average value is calculated as the green ball compressive strength.

[0049] Then the green balls are dried, preheated and roasted to obtain roasted pellets. Then the compressive strength of the roasted pellets is tested. The specific steps are as follows:

[0050] Ten roasted pellets from the same batch were selected, and the crushing pressure of each pellet was measured using a JHY-5000 electronic universal pressure testing machine. The pressurization speed was maintained at 10 mm / min, and the average value was calculated after removing the extreme values ​​to express the compressive strength, with the unit of "N / piece".

[0051] The present invention is further described below in conjunction with specific embodiments.

[0052] The pelletizing raw material components used in the following examples and comparative examples are as follows:

[0053] Based on 100 parts, the dried cobalt smelting waste slag includes the following components by mass: SiO2: 25.16 parts, Fe(OH)3: 33.65 parts, CaO: 13.92 parts, MnO: 0.65 parts, Al2O3: 2.79 parts, MgO: 2.91 parts, TiO2: 1.22 parts, P2O5: 1.32 parts, S: 5.08 parts, Na: 5.03 parts, Cl: 2.83 parts, Co: 0.84 parts, and the rest are unavoidable impurities;

[0054] Based on 100 parts, the magnetite includes the following components in parts by mass: TFe: 64.77 parts, SiO2: 2.07 parts, CaO: 0.78 parts, MgO: 0.72 parts, Al2O3: 1.09 parts, Na: 0.15 parts, and the rest are unavoidable impurities.

[0055] Based on 100 parts, the bentonite includes the following components in parts by mass: SO2: 70.36 parts, CaO: 2.74 parts, MgO: 2.47 parts, Al2O3: 18.03 parts, Na: 3.03 parts, TFe: 1.27 parts, and the rest are unavoidable impurities.

[0056] Example 1

[0057] The preparation method of the iron-containing binder of the present embodiment comprises the following steps:

[0058] (1) Weigh bentonite with a particle size of less than 0.074 mm and add it to water at a solid-to-liquid ratio of 1:5 to prepare a suspension.

[0059] (2) Add cobalt smelting waste slag with a particle size of less than 0.074 mm in a mass ratio of 3:7 to dry bentonite, stir thoroughly to disperse the cobalt smelting waste slag in water and enter the gel formed by the bentonite particles, and let it stand for 1 hour.

[0060] (3) The bentonite suspension was separated and purified by a centrifuge, and the solids were compacted and extruded by a screw extruder. After the extrusion was completed, the suspension was placed in a sample bag and aged for 3 days.

[0061] (4) After aging, the mixture was dried in an oven at 110° C. for 8 h, crushed in a ball mill, and sieved to obtain an iron-containing binder with a particle size of less than 0.074 mm.

[0062] The iron-containing binder is added into the pelletizing material to prepare pellets and the obtained pellets are tested for performance, which specifically includes the following steps:

[0063] Step 1: Prepare green pellets:

[0064] (1) screening the magnetite powder to control the magnetite powder to have a particle size of -0.074 mm and a mass percentage content of ≥98%, and then setting aside;

[0065] (2) The iron-containing binder and magnetite powder in this embodiment are uniformly mixed (the mass percentage of the raw ball dry material is: magnetite: 98%, iron-containing binder: 2%), and mist water is added to the mixture. The moisture content is controlled at 7.8%, and the mixture is pelletized at a speed of 20 r / min in a disc pelletizer with an inclination angle of 45° and a diameter of 800 mm to obtain raw pellets;

[0066] Step 2: Ball performance test:

[0067] 1) Raw ball drop strength test:

[0068] Select 12 green balls of similar size, test one green ball at a time, and let it fall freely from a height of 0.5m onto a 10mm thick steel plate. Counting starts from 0 times, and repeat the drop test until cracks appear on the green ball. The average value is calculated as the green ball drop strength.

[0069] 2) Green ball compressive strength test

[0070] The green ball compressive strength test is carried out according to ISO 700 standard on a green ball compressive strength tester (YHKC 2A model). 12 green balls of similar size are selected and one green ball is tested each time. The average value is calculated as the green ball compressive strength.

[0071] 3) Green ball burst temperature detection

[0072] The bursting temperature of green balls is determined by dynamic measurement method. 50 qualified green balls are randomly selected and placed in the test cup. The air temperature of the bursting furnace changes from low temperature to high temperature with a gradient of 20°C. After the air temperature stabilizes, the cup containing the small balls is placed in the exhaust heating furnace tube. The air is heated and flows through the small balls through the bottom of the cup to perform a burst test on the green balls. The cup is placed in the test chamber for 5 minutes. If the number of green balls that burst is 2, the corresponding temperature is the bursting temperature of the green balls in this test. A group of experimental balls is tested 3 times, and the average value of the three bursting temperatures is taken as the test index.

[0073] Step 3: Drying the raw balls

[0074] The qualified green balls are placed in a 300℃ forced air drying furnace for drying. The air velocity is 0.6m / s, the air time is 8min, and the number of green balls dried each time is 100.

[0075] Step 4: Preheating the pellets

[0076] The pellets were calcined in a tube furnace with a preheating temperature of 950 °C and a preheating time of 15 min.

[0077] Step 5: Pellet roasting

[0078] The pellets were calcined in a tube furnace at a temperature of 1250°C for 20 min.

[0079] Step 6: Performance test of roasted pellets

[0080] 1) Compressive strength test of roasted pellets

[0081] Ten roasted pellets from the same batch were selected, and the crushing pressure of each pellet was measured using a JHY-5000 electronic universal pressure testing machine. The pressurization speed was maintained at 10 mm / min, and the average value was calculated after removing the extreme values ​​to express the compressive strength, with the unit of "N / piece".

[0082] The performance test results of the pellets produced in this embodiment are shown in Table 1.

[0083] Comparative Example 1

[0084] The experimental process of this comparative example is the same as that of Example 1, except that the mass percentage of the iron-containing binder dry material is: bentonite: 100%, cobalt smelting waste slag: 0%. The properties of the pellets were tested, and the experimental results are recorded in Table 1.

[0085] Comparative Example 2

[0086] The experimental process of this comparative example is the same as that of Example 1, except that the mass ratio of cobalt smelting waste slag to bentonite dry material is 3:2. The properties of the pellets produced are tested, and the experimental results are recorded in Table 1.

[0087] Comparative Example 3

[0088] The experimental process of this comparative example is the same as that of Example 1, except that: the solids are not extruded by a screw extruder after being compacted. The properties of the pellets are tested, and the experimental results are recorded in Table 1.

[0089] Comparative Example 4

[0090] The experimental process of this comparative example is the same as that of Example 1, except that the solids are compacted and extruded by a screw extruder without aging. The properties of the pellets are tested, and the experimental results are recorded in Table 1.

[0091] Comparative Example 5

[0092] The experimental process of this comparative example is the same as that of Example 1, except that the dry cobalt smelting waste slag and bentonite are directly mechanically mixed together, water is added and stirred, and then a centrifuge is used to separate and purify the solid matter.

[0093] Example 2

[0094] The experimental process of this embodiment is the same as that of embodiment 1, except that the mass ratio of cobalt smelting waste slag to bentonite dry material is 1:4. The properties of the pellets produced are tested, and the experimental results are recorded in Table 1.

[0095] Example 3

[0096] The experimental process of this embodiment is the same as that of embodiment 1, except that the mass ratio of cobalt smelting waste slag to bentonite dry material is 1:1. The properties of the pellets produced are tested, and the experimental results are recorded in Table 1.

[0097] Table 1 Performance test results of green balls and metallized balls obtained in various embodiments and comparative examples of the present invention

[0098]

[0099] Combining the comparative analysis of pellet production quality indicators obtained from different schemes in Table 1, it can be seen that:

[0100] By comparing Examples 1-3 with Comparative Example 1, it can be seen that when the iron-containing binder prepared by combining cobalt smelting waste slag and bentonite is added to the pelletizing raw materials for pelletizing, the comprehensive performance indicators of the pellets are greatly improved. When the mass ratio of cobalt smelting waste slag and bentonite added is 1:1-1:4, the drop strength of the green ball is increased from 2.4 times / 0.5m in the benchmark experiment (Comparative Example 1) to 9.5 times / 0.5m, 8.9 times / 0.5m and 8.3 times / 0.5m respectively; the compressive strength of the green ball is increased from 6.1N / piece in the benchmark experiment to 14.6N / piece, 12.7N / piece and 13.6N / piece respectively; the burst temperature of the green ball is increased from 452°C in the benchmark experiment to 526°C, 513°C and 519°C respectively, and the compressive strength of the calcined pellets is increased from 2237N / piece in the benchmark experiment to 3018N / piece, 2918N / piece and 2937N / piece respectively.

[0101] Therefore, adding an iron-containing binder made from cobalt smelting waste slag and bentonite in a mass ratio of 1:1 to 1:4 to the pelletizing raw materials can significantly improve the comprehensive performance indicators of the pellets.

[0102] Combining Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the addition ratio of cobalt smelting waste slag and bentonite has an effect on the performance of the obtained pellets. When the mass ratio of cobalt smelting waste slag and bentonite is 3:2 to make an iron-containing binder and add it to the pelletizing raw material, compared with the solution of using only bentonite as a binder in Comparative Example 1, the green ball drop strength and green ball compressive strength are slightly improved, from 2.4 times / 0.5m and 6.1N / piece in the benchmark experiment (Comparative Example 1) to 3.2 times / 0.5m and 7.5N / piece; the green ball burst temperature is reduced from 452°C in the benchmark experiment to 439°C; the compressive strength of the calcined pellets is reduced from 2237N / piece in the benchmark experiment to 2081N / piece. However, compared with Example 1, it can be seen that the green ball drop strength and green ball compressive strength are not significantly improved, and the green ball burst temperature and the compressive strength of the calcined pellets are relatively low.

[0103] From Example 1 and Comparative Example 3, it can be seen that the process for preparing the iron-containing binder of the present invention is also crucial. When the iron-containing binder of the present invention is prepared without using a screw extruder to extrude the solid, the bursting temperature of the green balls decreases by 31°C and the compressive strength of the roasted balls decreases by 287N / piece.

[0104] In addition, in combination with Example 1 and Comparative Example 4, it can be seen that when the iron-containing binder is prepared without aging, the bursting temperature of the green balls decreases by 24°C and the compressive strength of the roasted balls decreases by 169N / piece.

[0105] It should be noted that the applicant has found through research that Fe(OH)3 contained in cobalt smelting waste slag is a hydrophilic substance, which can form a gel to bond iron ore particles and can be used as a binder for metallurgical pellets. Bentonite is added with water to form a gel, and the cobalt smelting waste slag is integrated into the bentonite. The two substances form a whole, thereby forming a more hydrophilic binder material, which plays a better hydrophilic role in the magnetite pelletizing process, thereby playing a better role in bonding mineral particles, achieving the effect of 1+1>2.

[0106] Furthermore, after the iron-containing binder of the present invention is spirally extruded during the preparation process, the montmorillonite particles of the bentonite are changed from a multilayer structure to a single-layer flaky structure, which has good fibrous connection characteristics. After aging treatment, the cobalt smelting waste residue will further penetrate into the interlayer of the bentonite. Through aging and pre-treatment of the bentonite, the montmorillonite layered structure in the bentonite can be effectively utilized, and the H2O formed by the decomposition of Fe(OH)3 is orderly exported with the help of the layered structure channel, avoiding the problem of the decrease in the burst temperature of the pellets. At the same time, the iron-containing binder contains elements such as Ca, Fe, and Si to form composite calcium ferrite during the roasting of the pellets, forming a liquid phase inside the roasted pellets, which is conducive to solid phase diffusion, promotes the recrystallization of hematite at high temperature, forms a large area of ​​hematite crystals, and enables the roasted pellets to obtain better compressive strength indicators.

[0107] In addition, the present invention also carried out the following experiments: Cobalt smelting waste slag and bentonite were simply physically mixed to obtain iron-containing binder A, and iron-containing binder B was obtained by mixing using the scheme of the present invention. The iron-containing binders A and B were added to magnetite to test the hydrophilicity and ball-forming properties of the raw materials. The hydrophilicity results of the mixture are as follows Figure 1 and Figure 2 As shown in Table 2 (it should be noted that the smaller the angle of the experimental detection, the stronger the hydrophilicity of the raw material), it can be seen that the hydrophilicity of the raw material when the ferrous binder B is added to the magnetite is better than that when the ferrous binder A is added to the magnetite, indicating that the ferrous binder obtained by the technical solution of the present invention has excellent performance. The results of the raw material ball-forming performance measurement are shown in Table 2 (it should be noted that the larger the raw material ball-forming index, the better the raw material ball-forming property). The results show that the ferrous binder B obtained by the technical solution of the present invention is added to the magnetite, and the ball-forming index of the mixture is significantly increased. The above results show that the mixture of cobalt smelting waste slag and bentonite can be made into an excellent ferrous binder by the technical solution of the present invention.

[0108] The specific test results of the hydrophilic contact angles of the above-mentioned iron-containing binder A and B raw materials are shown in Figure 1 and Figure 2 shown.

[0109] Table 2 Raw material balling performance test results

[0110] type Maximum capillary water Largest molecule water Balling index[Note 1] Balling evaluation 2% ferrous binder A + 98% magnetite 19.14 7.13 0.59 medium 2% ferrous binder B + 98% magnetite 19.47 8.31 0.74 good

[0111] Note 1: The static ball-forming index of a material refers to the ability of mineral powder to form balls when dripping water in a natural state. It is also a parameter for comprehensively evaluating the ball-forming performance of a material. It can reflect the specific surface area and hydrophilicity of the material and other various properties. K is usually used to represent the ball-forming performance of the material. It can reflect the specific surface area and hydrophilicity of the material and other various properties. K is usually used to represent the ball-forming performance of the material. Its value can be calculated by formula 1:

[0112]

[0113] Where: W 分 —Maximum molecular water, %; W 毛 —Maximum capillary water, %.

[0114] In summary, the present invention uses cobalt smelting waste slag produced in the cobalt smelting process and bentonite to mix and prepare an iron-containing binder, and the prepared iron-containing binder is used as a binder to make pellets, which are added to the subsequent blast furnace process. The present invention treats cobalt smelting waste slag through the existing industrial process, and the process is simple and easy to operate. It not only solves the problem of environmental pollution caused by cobalt smelting waste slag, but also improves the performance indicators of pellets, which plays a positive role in the existing process; the present invention has mature technology, no secondary pollution, small investment and low cost.

[0115] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.

[0116] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definition in this specification sheet shall prevail. When rate, pressure, temperature, time or other values ​​or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values ​​and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.

Claims

1. A method for preparing an iron-containing binder for metallurgical pellet preparation, characterized in that: The following steps are involved: Step 1: prepare bentonite suspension; Step 2: adding cobalt smelting waste slag to the bentonite suspension, stirring thoroughly, and standing for treatment; Step 3, separating and purifying the bentonite suspension containing cobalt smelting waste after standing, and performing spiral extrusion after compacting the purified solids, and performing aging treatment after the extrusion is completed; Step 4: drying after aging to obtain an iron-containing binder.

2. The method for preparing the iron-containing binder according to claim 1, characterized in that: The mass ratio of cobalt smelting waste slag to bentonite dry material is 1:1 to 1:

4.

3. The method for preparing the iron-containing binder according to claim 1, characterized in that: The particles of cobalt smelting waste slag are smaller than 0.074mm, accounting for more than 98%.

4. The method for preparing the iron-containing binder according to claim 1, characterized in that: The mass content of Fe(OH)3 in cobalt smelting waste slag is not less than 30%.

5. The method for preparing the iron-containing binder according to claim 4, characterized in that: The bentonite particles with a particle size of less than 0.074 mm account for more than 98%.

6. The method for preparing the iron-containing binder according to claim 1, characterized in that: When preparing bentonite suspension, bentonite and water are prepared according to a solid-liquid ratio of 1: (5-8).

7. The method for preparing the iron-containing binder according to any one of claims 1 to 6, characterized in that: After adding cobalt smelting waste slag to the suspension, the suspension is left to stand for 1-2 hours.

8. The method for preparing the iron-containing binder according to any one of claims 1 to 6, characterized in that: The aging time is 2d to 3d.

9. A ferrous binder, characterized in that: The method is prepared according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Double-polymer iron ore pellet organic binder and method for using same

    CN101693950B

  • Organic adhesive and blast furnace ironmaking pellet prepared from same

    CN104357656A

  • Polymerized bentonite binder for metallurgical pellets and preparation method and application thereof

    CN115094235B